2012
DOI: 10.1155/2012/854795
|View full text |Cite
|
Sign up to set email alerts
|

Association of Autoantibodies to BP180 with Disease Activity in Greek Patients with Bullous Pemphigoid

Abstract: 39 bullous pemphigoid (BP) patients were studied to assess the clinical significance of anti-BP180 and anti-BP230 circulating autoantibodies of BP and correlate their titers with the clinical scores of the BP Disease Area Index (BPDAI) and the Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) as well as with the intensity of pruritus measured by the BPDAI pruritus component. All parameters were evaluated by the time of diagnosis (baseline), month 3, and month 6. Titers of anti-BP180 autoantibodies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 17 publications
5
26
2
Order By: Relevance
“…At baseline, BPDAI mean scores were similar in both studies, and anti-BP180 and anti-BP230 ELISA values were consistent with previous reports [10,22,27,28,29]. Likewise, at baseline, we did not find a correlation between BPDAI and anti-BP230 ELISA values, which is consistent with the results obtained by Patsatsi et al [16]. Collectively, these results were in accordance with previous studies, which showed that titres of anti-BP180 autoantibodies were correlated with disease activity assessed by the number of daily new blisters, pruritus intensity or disease duration [10,27,30,31].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…At baseline, BPDAI mean scores were similar in both studies, and anti-BP180 and anti-BP230 ELISA values were consistent with previous reports [10,22,27,28,29]. Likewise, at baseline, we did not find a correlation between BPDAI and anti-BP230 ELISA values, which is consistent with the results obtained by Patsatsi et al [16]. Collectively, these results were in accordance with previous studies, which showed that titres of anti-BP180 autoantibodies were correlated with disease activity assessed by the number of daily new blisters, pruritus intensity or disease duration [10,27,30,31].…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, anti-BP180 and anti-BP230 autoantibodies were detected by ELISA at baseline, and then at months 3 and 6, and correlated both with BPDAI score and Autoimmune Bullous Skin Disorder Intensity Score [16]. At baseline, BPDAI mean scores were similar in both studies, and anti-BP180 and anti-BP230 ELISA values were consistent with previous reports [10,22,27,28,29].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations